PILIHAN RASIONAL PETANI MISKIN PADA MUSIM PACEKLIK - Sri Rejeki (UNIVERSITAS SEBELAS MARET (UNS), 2019)
The problems examined in this study are twofold, what are the factors that cause poverty in Kaligede Village, Senori District, Tuban Regency and What are the strategies for the survival of poor farmers during a lean season. The method used is descriptive qualitative with the method used is a descriptive qualitative method with data collection techniques of observation, interviews, and documentation. The theory used in looking at the phenomena that occur in poverty and the survival strategy of poor farmers in a famine season in Kaligede Village, Senori District, Tuban Regency is the Rational Choice Theory of James. S Colemen and David McClelland's Needs Achievement Theory. From the results of this study it was found that; (1) There are several factors causing poverty that are divided into two parts, namely cultural factors and structural factors. Because cultural factors are low education, low human resources, lack of job diversification, low achievement spirit. Meanwhile, structural factors are the lack of jobs and uneven assistance. (2) The survival strategy undertaken by poor farmers in the lean season is to take firewood in the forest, owe it to meet their daily lives, and also migrate to big cities. Keywords: Farmers, Rational Choices, Needs for Achievement AbstrakPermasalahan yang dikaji dalam penelitian ini ada dua yaitu apa saja factor penyebab kemiskinan di Desa Kaligede Kecamatan senori Kabupaten Tuban dan Bagaimana strategi bertahan hidup petani miskin pada musim paceklik. Metode yang digunakan ialah deskriptif kualitatif dengan Metode yang digunakan adalah metode deskriptif kualitatif dengan teknik pengumpulan data observasi, wawancara, dan dokumentasi. Teori yang digunakan dalam melihat fenomena yang terjadi pada kemiskinan dan strategi bertahan hidup petani miskin pada musim paceklik di Desa Kaligede Kecamatan Senori Kabupaten Tuban ini ialah Teori Pilihan Rasional James. S Colemen dan Teori Kebutuhan Prestasi David McClelland. Dari hasil penelitian ini ditemukan bahwa; (1) Terdapat beberapa faktor penyebab kemiskinan yang dibagi menjadi dua bagian yaitu faktor kultural dan faktor struktural. Sebab faktor kultural ialah rendahnya pendidikan, sumber daya manusia rendah, tidak adanya diversifikasi pekerjaan, semangat prestasi rendah. Sedangkan sebab faktor struktural ialah kurangnya lapangan pekerjaan, dan bantuan tidak merata. (2) Strategi bertahan hidup yang dilakukan oleh petani miskin pada musim paceklik ialah dengan mengambil kayu bakar di hutan, berhutang untuk memenuhi kehidupan sehari-hari, dan juga merantau ke Kota-kota besar. Kata kunci: Petani, Pilihan Rasional, Kebutuhan Prestasi